KIPRAH SUDHARMONO DALAM SEJARAH GOLONGAN KARYA (1983-1988) - Adisthy Regina; Andi Suwirta (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2018)
The main problem discussed in this study, “how was the role of Sudharmono in leading the Golongan Karya (1983-1988)”. The research method used was the historical method including heuristics, source criticism, interpretation, and historiography. Based on result’s study, Sudharmono was Soeharto’s right-hand man in New Order’s era. This proven with the candidacy of Sudharmono as Golkar Chairman from 1983-1988, that was directly elected by Soeharto. Sudharmono was a figure who contributed to Golkar’s progress in the New Order (1983-1988). Sudharmono was a Chairman from civilian,however, he could take Golkar to maximum advancement. These advancements were made because Sudharmono had taken formal and non-formal education with tremendously well. His great accomplishments made Sudharmono become a figurewho could work more. Sudharmono has made Golkar better through his policy called Tri Sukses Golkar, such as Sukses Konsolidasi, Sukses Repelita IV and Sukses Pemilu 1987, as well as General Assembly of MPR 1988. The policy that made by Sudharmonohave connectedness because if consolidation succeeded, it would affect success for other policy namely Repelita and the General Election of 1987. A great victory of Golkar in General Election of 1987, had succeeded made Sudharmono became the Vice President of the Republic of Indonesia in 1988. This accomplishment became a threat to Soeharto because he could replace him from the presidency position. To prevent such action, Soeharto forbade Sudharmono to proposed back to became Golkar’s Chairman for 1988-1993 period.